Atherosclerotic vascular disease in systemic lupus erythematosus. - Liang, Matthew H. (National Medical Association, 2002)
In the United States, systemic lupus erythematosus (SLE) disproportionately affects African Americans. It has become a chronic disease with long-term morbidity including chronic renal disease, osteoporosis, cataracts, psychosocial impairment, and importantly, atherosclerotic vascular disease (ASVD). The latter (myocardial infarction, angina, peripheral vascular disease and stroke) are strikingly accelerated, occurring in subjects who are predominantly premenopausal women at an age when ASVD is rare or unusual. Although much is known about the biology, risk factors, and the prevention of atherosclerosis in normal individuals, little work has been done in SLE. In fact, ASVD in people with SLE may be a different disease. Approximately 1.5% of SLE patients per year will have a myocardial infarction or equivalent; about 0.5% of SLE patients per year will have a stroke. The risk factors for ASVD in SLE are based on small, retrospective, single center studies. These suggest that the risk factors known for the general population (i.e., smoking, obesity, sedentary lifestyle, high LDL cholesterol, etc.) are also observed in SLE. The best study of risk factors shows that even accounting for the known factors, SLE and/or its treatment (glucocorticoids) is by far the most important. Our current management of cardiovascular risk factors in SLE patients with ASVD is substandard and our adherence to national guidelines for prevention is substandard. It is not known whether improving either will prevent these disastrous outcomes. Very little is known about the risk factors in African Americans with SLE, although there is data to suggest that they may not be identical to those seen in Caucasian populations. The study of the best and most effective means to prevent ASVD in SLE and in African Americans with SLE and in African Americans with SLE should be a major priority.